The Influence Of Taxation Knowledge, Taxpayer's Income, And Quality Of Motor Vehicle Service Access On Taxpayer Compliance (Study At The North Lombok Joint Samsat Office) - Denda Gesva Meisi Noni; Adhitya Bayu Suryantara (Citakonsultindo, 2024)
This research was conducted to determine the influence of taxation, taxpayer income, and quality of service access on taxpayer compliance at the North Lombok Joint Samsat Office. This research uses a quantitative type of research. The data used is primary data and secondary data. The sample obtained in this research was 100 respondents. The sampling technique uses random sampling with the sample size calculated using the Slovin formula. Data analysis in this study used multiple linear regression analysis with the help of SPSS 26. The findings of this research are that knowledge of taxation and quality of service access have a positive and significant influence on motor vehicle taxpayer compliance, while taxpayer income has no significant influence on vehicle taxpayer compliance. motorized